Storytelling and Education in the Digital Age Experiences and Criticisms - Stocchetti, Matteo (Peter Lang International Academic Publishing Group, 2016)
While the importance of the role of storytelling can hardly be overestimated, the impact of digitalization on this role is more ambivalent. In this second book-length publication of the programme Media and Education in the Digital Age - MEDA, the authors take a critical stance towards the alleged emancipative affordances of digital storytelling in education. The collection is inspired by the effort of making professional educators aware of the risks of the digital turn in educational storytelling but also of the opportunities and the conditions for critical engagements. Based on their research and field experience, fifteen scholars discuss in nine chapters these risks and opportunities, providing ideas, evidence, references and inspiration to educators and researchers.